Modelling control systems using IEC 61499 - Zoitl, Alois; Lewis, R. W. (The Institution of Engineering and Technology, 2014)
The main objective of this book is to widen the understanding of the most important concepts in the IEC 61499 standard and to show how these concepts can be applied to industrial problems. IEC 61499 is a complex standard that defines many new concepts related to function blocks and the supporting architecture in a rigorous and thorough manner - as a consequence, the standard can be difficult to understand by people who read it for the first time. This book has therefore concentrated on the main concepts and has intentionally summarised or omitted some of the less significant details in the standard. For this reason, some topics such as the Textual Syntax for describing function block definitions have not been covered in great detail. IEC 61499 provides, for the first time, a framework and architecture for describing the functionality in distributed control systems in terms of co-operating networks of function blocks. It is the authors' intention that the benefits of this standard should be understood by a wide audience; including not only people working in industrial control and also those with a general interest in methodologies for modelling distributed systems.